Case Report: Ischemic brain infarction and cognitive dysfunction syndrome in an aged dog - Kang, Min-Hee; Jeong, Woo-Phil; Nam, Chan-Sik; Yoon, Jun-Won; Choi, Dong-Min; Lee, Gwang-Seob; Kim, Yeon-Jin; Dan, Tae-Jung; Park, Hee-Myung (Frontiers in Veterinary Science, 2025)
This case report describes a rare occurrence of canine cognitive dysfunction syndrome (CDS) accompanied by ischemic brain infarction, providing insights into the relationship between neurodegeneration and cerebrovascular pathology in aged dogs. A 19-year-old neutered male miniature poodle exhibited progressive behavioral changes over three years, including nocturnal restlessness, inappropriate urination, and aimless wandering. Neurological examination revealed mild disorientation, decreased proprioception, and weakened postural reactions in the hind limbs, with a cognitive dysfunction rating (CDDR) score of 64 indicating severe cognitive impairment. Magnetic resonance imaging (MRI) revealed hallmark indicators of brain atrophy, such as widened cerebral sulci and ventricular enlargement, along with multifocal ischemic lesions in the right parietal and occipital area. Histopathological findings confirmed widespread neurodegeneration, including severe vacuolation and neuronal necrosis in the precentralis interna and anterior subcallosal regions. Congo Red-positive staining identified amyloid-like deposits in cerebral vessels, and Lewy bodies in the brainstem suggested concurrent vascular and amyloid pathology. This case provides evidence of a potential connection between cerebrovascular pathology and CDS, indicating that ischemic and hemorrhagic lesions may aggravate neurodegeneration and contribute to cognitive and neurological deficits. The coexistence of brain infarction and amyloid deposits in this dog resembles pathological processes observed in human conditions such as Alzheimer’s disease and vascular dementia, highlighting the multifactorial nature of CDS. Advanced neuroimaging and histopathological analysis were critical in diagnosing and understanding this complex interaction. Further research is needed to clarify the mechanisms linking neurodegeneration and cerebrovascular disease in aging dogs.